Current status and barriers to fisheries comanagement: Evidences from an Oxbow lake of Bangladesh (Bangladesh Journal of Zoology, 2018)
Co-management of common property aquatic habitats are increasingly implemented with a view to increasing fish production, ensuring fishers’ rights and to conserve biodiversity. This study investigates the current status and identifies barriers to fisheries management in an oxbow lake (baor) at Jessore district, Bangladesh. Using interviews, focus group discussions and secondary data, this study revealed that both capture and culture fisheries are practised at the same time at the same water-body. As the wetland was used solely for capture fisheries before, the introduction of aquaculture practice has increased the total fish production and income for some people. However, it has reduced the access to poor fishers and fish biodiversity. Particularly the biodiversity of Channa sp, Puntius sp, Mastacembelus sp, Mystus sp, and Colisa fasciatus has been reduced. A range of climatic, institutional, economic and social barriers have facilitated the reduced access of poor fishers and biodiversity. To overcome the barriers and ensure sustainable management of the baor this study proposes to implement a fair leasing system, increase financial and human resources together with an ecosystem-based approach to baor management.Bangladesh J. Zool. 46(2): 105-116, 2018